Phytochemical profiling and antioxidant capacity of Achillea Santolina at different phenological stages - Nasrin Farhadi; Mohammad Moghaddam; Sara Farsaraei; Khyrollah Babaei; Abdollah Ghasemi Pirbalouti (Scientific Reports)
Abstract In the present study, the phytochemical quantity and quality as well as the antioxidant capacity of Achillea santolina at different growth stages including vegetative, flowering, and fruit set were investigated. The leave methanolic extraction of harvested plants at the flowering stage showed the highest phenolic and flavonoids content. The content and composition of A. santolina essential oil was varied depending on the plant development stage. The highest essential oil content (0.3% v/w) was obtained in the harvested aerial parts at the flowering stage followed by fruit set and vegetative stages. According to results of GC-FID and GC-MS, oxygenated monoterpenes represented by 1,8-cineole, α-thujone, and camphor were the predominant compounds in the A. santolina essential oil, which comprised 69.63–88.61% of the total oil composition. The essential oil quality of A. santolina was varied during the growing season and the observed variation was related to the differences in concentrations of main compounds and occurrence of minor constituents. An ascending and descending trend respectively was found regard to monoterpene and sesquiterpene contents during the growing life cycle of A. santolina and the highest ratio of these compounds was obtained at the fruit set stage. The total phenol content and antioxidant capacity of A. santolina essential oils gradually increased during the plant growth period that reached a maximum value at the fruit set stage. According to obtained results, appropriate harvesting stage can be chosen based on application purpose regards to essential oil quantity or quality. The results suggests that the flowering and fruit set stages can be considered as suitable sources of highest essential oil content and antioxidant potential, respectively.